Exploring student teachers’ experiences of vulnerability in higher education spaces - de Jager, S. (South African Journal of Higher Education, 2023)
Recently, scientific interest in higher education students’ wellbeing has increased. The highlighted issues include professional development, professional identity, and personal behaviour. The significance of this study relates specifically to supporting students’ wellbeing by gaining an understanding of factors contributing to their experiences of vulnerability. Through the arts-informed methodology of Photovoice, which emerges from community-based participatory research, 16 student teachers explored the concept of vulnerability in the context of a higher education institution. The research project required student teachers to take photos of that which represents what they perceive as vulnerability. Student teachers explored their personal, school and campus space with this project. Ultimately, this research speaks to the Sustainable Development Goal of good health and wellbeing, which seeks to promote wellbeing across the individual life span, and ensure healthy lives, as well as the Sustainable Development Goal of quality education, which emphasises the need to improve quality of life and quality teacher training.